Avicennia Genetic Diversity and Fine-Scaled Structure Influenced by Coastal Proximity of Mangrove Fragments - Ludwig Triest; Alieza Del Socorro; Alieza Del Socorro; Vincent Jay Gado; Vincent Jay Gado; Analyn M. Mazo; Tim Sierens (Frontiers in Marine Science, 2021)
Avicennia dominated mangrove forests occur from seaward to landward sites and hence are subject to different dynamics within estuarine ecosystems. Regeneration of mangrove forests primarily depends on the extent of propagule spread and subsequent establishment in suitable habitats. The complex nature of estuarine systems induces a wide variety of local conditions for within-site propagule retention and settlement thereby allowing spontaneous regeneration of mangroves. In this study, we estimated the fine-scale spatial genetic structure (FSGS) of Avicennia populations and examined whether their position relative to the seaside or the size of mangrove patches could have influenced the extant local population genetic structure. A kinship-based FSGS was performed using microsatellite markers in 523 A. marina, 189 A. rumphiana and 60 A. alba adult trees of 24 sites in The Philippines. Transects within each estuary were taken both parallel and perpendicular to the coastline or tidal river edge. The extent of local mangrove areas and various human-induced encroachments as such did not show any trend in allele diversity, heterozygosity values or inbreeding levels. However, farther inland situated mangrove patches showed a larger FSGS extent across the neighborhood (up to 75 m) though less diversity along with inbreeding, most likely due to retention of related propagules and lowered chance of external propagule input. Estimation of connectivity along a same coastline stretch supported a unidirectional steppingstone or adjacent migration model for populations of either A. marina, A. alba or A. rumphiana. These were congruent with ocean currents across mangrove estuaries of the Tablas Strait and along Western Leyte, thereby emphasizing the relevance of coastal connectivity for long term persistence. From this study, we conclude that both proximity to open water and narrowness of mangrove patches may affect their captured diversity, inbreeding and fine-scale structure caused by propagule movement within or beyond a local mangrove fragment during recent generations. Higher levels of allele diversity for seaward sites and highest likelihood of migration for adjacent mangroves both add to the importance of coastal connectivity that is the only natural cohesive force on longer term and necessary to counteract short term effects of increasingly encroached mangrove environments.